Electromagnetic wave absorption of inexpensive C/ZnO composites derived from zinc-based acrylate resins. Issue 19 (1st October 2021) - Zhou, Wenjun; Liu, Ning; Li, Cuiping; Yu, Liangmin; Zhang, Zhiming; Li, Changcheng; Yan, Xuefeng
Abstract: Based on the abundant and low-cost zinc-based acrylate resins, C/ZnO composites were fabricated via one-step carbonization at 700 °C in a N2 atmosphere for 2 h. Zinc-based acrylate resins, which were synthesized by free-radical polymerization of butyl acrylate (BA), acrylic acid (AA) and vinyl acetate (VAc) and dehydration condensation of Zn(OH)2, provided a common source for carbon and ZnO. These materials demonstrate enhanced electromagnetic wave absorption (EMWA) behavior with tunable microwave absorption bands at 2–18 GHz, which is related to the molar ratio (mol%) of Zn(OH)2 to acrylate monomers in zinc-based acrylate resins. Remarkably, the 0.11 mol% C/ZnO composite exhibits outstanding absorption properties: the minimum reflection loss (RLmin ) at 16.7 wt% loading of −34.66 dB is observed at 3.0 mm and 10.32 GHz, and an RLmin of −24.83 dB is observed at a small thickness of 1.5 mm with an effective absorption bandwidth (EAB) of 3.61 GHz. Moreover, the EAB (RL ≤ −10 dB) from the C band to Ku band is achieved by simply adjusting the thickness of the absorbers, which are superior to the other hybrids of organic carbon and ZnO. These results provide a new strategy for the preparation of carbon-based composites containing metal oxides and their application in high-performance microwave absorption. Graphical abstract: Image 1 Highlights: Zinc-based acrylate resins were first applied as precursors to prepare C/ZnO composites for electromagnetic absorption. Effective adsorption of C/ZnO composites could be tuned by adjusting the molar ratio of Zn(OH)2 to acrylate monomers. An RLmin value at 16.7 wt% loading of -34.66 dB (10.32 GHz) at 3.0 mm and EAB of 3.61 GHz at 1.5 mm were achieved. The EMWA mechanism of the C/ZnO composites was investigated in detail.